Blockchain-Based Waqf and Maslahah Mursalah: A Sharia Analysis in Light of MUI Fatwas - Widyarta Wijaya, Muhammad; Ramis, Irfan; Rohmaningtyas, Nurwinsyah; Ghozali, M. Lathoif (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2025)
Despite Indonesia’s vast waqf potential, asset management remains inefficient due to persistent issues of transparency, accountability, and public trust. This study examines the integration of blockchain technology within waqf management and its legitimacy under Islamic law, analyzed through the lens of maslahah mursalah and Majelis Ulama Indonesia (MUI) fatwas. Previous studies on blockchain waqf have largely focused on technical feasibility and governance frameworks, yet have not sufficiently addressed its shariah legitimacy through usul fiqh reasoning. Employing a qualitative-descriptive method, the research integrates four analytical stages: (1) textual analysis of Qur’anic and Prophetic principles on transparency and trust (amanah), (2) review of MUI fatwas to identify legal boundaries for digital financial instruments, (3) comparative analysis of blockchain-based waqf models from Malaysia, Turkey, and the UAE, and (4) conceptual synthesis aligning technological transparency with the objectives of maslahah mursalah. Findings suggest that blockchain, when implemented within a shariah-governed framework, fulfills the criteria of public benefit and does not contravene existing fiqh principles, thus qualifying as a legitimate ijtihadi innovation (tathbiq al-maslahah). The study concludes that blockchain-based waqf has the potential to strengthen institutional credibility, enhance transparency, and optimize social welfare distribution. This research contributes to the development of sharia-compliant digital philanthropy frameworks in Indonesia and offers policy insights for the digital transformation of Islamic social finance institutions